Sifat tekan komposit sandwich dengan inti beton cellular diperkuat pin bambu sebagai bahan panel ringan - Catur, A.D.; Sutanto, R.; Salman, S.; Sari, N.H.; Wijana, M.; Prijaya, M.T. (Universitas Mataram, 2023)
Cellular lightweight concrete as sandwich composite core has the advantage of its density, with the presence of foam which makes it lighter. However, the presence of foam reduces its strength. Reinforcement with bamboo pins was carried out to increase the compressive strength of the sandwich composite. Bamboo pins connecting the composite skin reinforce the cellular lightweight concrete at an angle of 900, 700,650 to the composite skin. With the addition of bamboo pins, it increases the compressive strength of the sandwich composite in both flat and edge directions.